STRATEGI PENGUATAN KELOMPOK TANI NGUDI RAHARJO III DI DESA LEMBERANG, KECAMATAN SOKARAJA, KABUPATEN BANYUMAS - Lutfi Zulkifli; Rifki Andi Novia (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
In this research, the authors will propose several appropriate strategies for strengthening the Ngudi Raharjo III Farmer Group in Lemberang Village, Sokaraja District, Banyumas Regency, Central Java. The proposed strategy will be compiled based on IFE and EFE analysis, SWOT, and QSPM analysis to get the strongest strategy and can be a top priority to be implemented in strengthening the empowerment of farmer groups. This research is expected to provide the right solution to empower and maximize the potential of farmer groups so that the benefits can be felt for all group members. After identifying external and internal factors, the next strategy analysis is a SWOT strategy analysis. As the resulting strategy from the SWOT analysis for strengthening the Ngudi Raharjo III Farmer Group, a QSPM produced a priority strategy from the existing strategy. Assistance by agricultural experts from Jenderal Soedirman University was the main strategy and a priority to be carried out with the highest Sum Total Attractiveness Scores (STAS) among other strategies on QSPM Analysis, amounting to 6.91.